Islamic Leadership Management on Business - Antonio, Muhammad Syafii (Business and Sustainability, 2022)
When the New Order regime was toppled, Indonesia entered a new historical phase known as the reformation era. Indeed, the ‘reformasi era’ was the antithesis of the New Order era. Reformers wanted to fix everything that had gone wrong under the Suharto regime. Many hopes were raised that the fate of the nation would be better and the various problems inherited from the previous era could be resolved. The spirit of reformasi made many things that were previously considered impossible during the New Order era find an outlet. At the beginning of the reformation, a number of previously impossible ideals such as (1) the superiority of ethics and morals over power, (2) the victory of change over the establishment, (3) hope for the future over the darkness of the past, (4) the triumph of conscience over the abuse of power in the past. The following study will try to put forward some ideas that we may already know together to build Indonesia to become a more victorious, respected, and dignified nation, namely by strengthening human capital with faith, hard work, and professionalism.